Republic of Armenia : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This paper describes that with the global downturn in 2007-2009, some of these achievements were partially reversed due to severe negative shocks to growth and changes in the composition of growth. While compared to peer countries, inequality in Armenia remains low; it has increased somewhat since 2009. Poverty has marginally declined after the global crisis, but unemployment remains high. Creating jobs, reducing poverty, and higher inclusiveness would require sustained high growth and implementing pro-poor policies. Better-targeted social policies and more attention to the regional distribution of spending would also help reduce poverty and improve inclusiveness. Poverty declined during the 2000s, supported by high growth. Poverty rate decreased by one third and the extreme poverty declined by half during 2004-2008. In addition to strong growth which created many job opportunities, higher social expenditures played a key role in lowering poverty. Regional disparities of poverty levels remain very high. These disparities, however, are geographical and not across the urban/rural divide. Indeed, contrary to the common perception, poverty rates in urban and rural areas are almost the same.